VD_FINDINFO Jug / 2020 / 302 vom 7. Januar 2020 - VD Tribunal cantonal (2020)
ACQUITTEMENT, IRRESPONSABILITÉ, CIRCULATION ROUTIÈREDROIT DE LA CIRCULATION ROUTIÈRE, NÉGLIGENCE | 12 al. 3 CP, 19 CP, 90 al. 1 LCR, 91 al. 2 LCR, 91a al. 1 LCR, 92 al. 1 LCR